Cambodia Economic Update, October 2017 : Cambodia Climbing Up the Manufacturing Value Chains - World Bank Group (World Bank, Phnom Penh, 2017)
Growth remains robust, but is projected to ease slightly to 6.8 percent in 2017, comparedwith 7.0 percent in 2016. Exports of clothing and other textile products have moderated andthe construction sector is showing signs of easing. Offsetting deceleration in the exports ofclothing and other textile products, is the rising share of non-textile product exports, especiallythe exports of electrical machinery, equipment and auto parts, attracted by improvedconnectivity and access to a more reliable energy supply. Efforts to increase tourism potentialseem to be paying off with a marked increase in the arrival of foreign tourists. Real growthis projected to remain strong, expanding at 6.9 percent in 2018. The medium-term outlookremains positive, boosted by export diversification and underpinned by healthy inflows offoreign direct investment (FDI) and an improving global outlook. A possible slowdown ofthe regional economy, especially China, and potential election-related uncertainties posedownside risks to the outlook.